2006
DOI: 10.1161/circulationaha.105.001529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Undersized Mitral Annuloplasty on Regional Transmural Left Ventricular Wall Strains and Wall Thickening Mechanisms

Abstract: Background-Undersized mitral annuloplasty, widely used for ischemic and functional mitral regurgitation (MR), has been proposed as an "annular solution to a ventricular problem." Beyond relief of MR, it is thought to improve global left ventricular (LV) shape, hence potentially reducing myocardial stress and promoting beneficial reverse LV remodeling. We previously observed that undersized annuloplasty inhibited systolic wall thickening at the LV base near the mitral annulus. In this study, we measured the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
(29 reference statements)
1
17
2
Order By: Relevance
“…We observed papillary muscle repositioning with this intervention, and it is not unreasonable to conjecture that such would also be the effect of the Geoform prosthesis consistent with improved coaptation borne out in mathematical modeling studies [13]. Undersized suture annuloplasty with 20% SL diameter reduction, however, has been associated with reduced anterobasal myocardial fiber shortening in experimental animals [21] suggesting a possible deleterious effect on local LV function. Similarly, isolated SL cinching of the central valve diameter reduces LV systolic wall thickening near the mitral annulus [22].…”
Section: Discussionsupporting
confidence: 58%
“…We observed papillary muscle repositioning with this intervention, and it is not unreasonable to conjecture that such would also be the effect of the Geoform prosthesis consistent with improved coaptation borne out in mathematical modeling studies [13]. Undersized suture annuloplasty with 20% SL diameter reduction, however, has been associated with reduced anterobasal myocardial fiber shortening in experimental animals [21] suggesting a possible deleterious effect on local LV function. Similarly, isolated SL cinching of the central valve diameter reduces LV systolic wall thickening near the mitral annulus [22].…”
Section: Discussionsupporting
confidence: 58%
“…Experimental studies have demonstrated increased strains on the posterior annulus and leaflet following restrictive annuloplasty which further predisposes to leaflet immobility and tethering. 18, 19, 25, 26 …”
Section: Discussionmentioning
confidence: 99%
“…Data from animal studies has been used to improve annuloplasty ring design but technological limitations have precluded the performance of such analyses for routine clinical use 38 . Our performance of these analyses in a timely fashion brings us a step closer to incorporating this information into clinical decision-making and objectively assessing the concept of offering an ‘annular solution to a ventricular problem’ 19 .…”
Section: Commentmentioning
confidence: 99%
“…Ideally, geometric distortion of the mitral annulus incurred from annuloplasty devices should also be objectively quantified and followed. But despite recognition of the prognostic value of mitral annular changes in FMR, technological impediments have precluded their clinical application 19 . Demonstration of differences in mitral annular geometry (static and dynamic) between patients with and without FMR in a clinically feasible fashion should be the first step towards achieving this goal.…”
Section: Introductionmentioning
confidence: 99%